Aproximación teórica al estudio de la literatura rusa - Hita Jiménez, José Antonio (Eslavística Complutense, 2003)
This article treates of the principal methodological and theorical criteria applicable to the study of the history of Russian literature seen in the perspective of historical evolution of Russian literature and Russian literary critical and the universal meaning of Russian literature. It gives special emphasis to the most important aspects of the evolutionary process of Russian literature which are over the traditional expositions and offers good perspectives for future research.